CarbonSink+: Accounting for multiple climate feedbacks from forests - Kulmala, Markku; Ezhova, Ekaterina; Kalliokoski, Tuomo; Noe, Steffen; Vesala, Timo; Lohila, Annalea; Liski, Jari; Makkonen, Risto; Bäck, Jaana; Petäjä, Tuukka; Kerminen, Veli-Matti (Finnish Environment Institute, 2021)
Forests cool the climate system by acting as a sink for carbon dioxide (CO2) and by enhancing the atmospheric aerosol load. whereas the simultaneous decrease of the surface albedo tends to have a warming effect. Here, we present the concept of CarbonSink+. which considers these combined effects. Using the boreal forest environment as an illustrative example, we estimated that accounting for the CarbonSink+ enhances the forest CO2 uptake by 10-50% due to the combined effects of CO2 fertilization and aerosol-induced diffuse radiation enhancement on photosynthesis. We further estimated that with afforestation or reforestation, i.e., replacing grasslands with forests in a boreal environment, the radiative cooling due to forest aerosols cancels most of the radiative warming due to decreased surface albedos. These two forcing components have. however, relatively large uncertainty ranges. resulting in large uncertainties in the overall effect of CarbonSink+. We discuss shortly the potential future changes in the strength of CarbonSink+ in the boreal region, resulting from changes in atmospheric composition and climate. Peer reviewed